Five year outcome of preterm sextuplets related to size at birth. Issue 4 (April 1990) - Marlow, N; Ellis, A M; Roberts, B L; Cooke, R W
Abstract : Preterm sextuplets were studied to examine whether growth retardation affects long term outcome. All were growing normally at 5 years. Intelligence quotients (IQ) ranged from 105-116 and motor impairment scores from 1.0-7.0. No neurological or behavioural abnormalities were found. The largest sextuplet has maintained her position for growth and IQ. No relation between test scores and birth weight or perinatal variables was found in the remaining siblings.